Modes of reactivity of cyclic diynes: probing the syn/anti selectivity of tetrathiacycloalkadiynes and mono(alkyne)cobalt complexes - Benisch, Christoph; Werz, Daniel B.; Gleiter, Rolf; Rominger, Frank; Oeser, Thomas (European journal of inorganic chemistry, 2003)
Cyclic tetrathiaalkadiynes in which two 1,4-dithiaalkyne units are connected with alkane bridges of length n and m [A(m.n)] were treated with [?2-bis(tert-butylsulfonyl)acetylene]carbonyl(?5-cyclopentadienyl)cobalt(I) (8a) and several substituted analogues (8b?8e) in order to probe the reactivity of electron-rich cyclic diynes. Both mono- [B(m.n)] and bis(cyclobutadiene) [C(m.n)] complexes were isolated as products of these reactions and the anti/syn ratio of C(m.n) was determined. For m, n < 4 the syn isomers dominate and this is attributed to the configuration of the intermediate metallacycle which is correlated with the conformations of the rings in the mono(cyclobutadiene) products B(m.n). This analysis was corroborated by X-ray structural investigations of the products. (? Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003)
Gesehen am 22.10.2020